2015
DOI: 10.1016/j.solidstatesciences.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of polymorphism and thermal behavior of CaZr(PO4)2

Abstract: The crystal structure of CaZr(PO 4 ) 2 has been revised by ab initio Rietveld analysis of X-ray powder diffraction data. At room temperature, CaZr(PO 4 ) 2 crystallizes in the orthorhombic space group Pna2 1 (Z = 4). Differential thermal analysis suggests a reversible second order transition at 1000°C confirmed by high temperature XRD analysis that brings out the existence of a high temperature form, very similar to the room temperature one, but more symmetrical (Pnma, Z = 4). Analysis of the crystal parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…high thermal and chemical stability, high radiation resistance and insignificant leachability by water. [1][2][3][4][5][6][7][8] Rich crystal chemistry of phosphates with the variation of nature and ionic radius of cations have been explored in several reports. [6][7][8] In particular such phosphates with tetravalent ions form densely packed structure and they are amenable for immobilization of various actinides, like uranium, neptunium and plutonium.…”
Section: Introductionmentioning
confidence: 99%
“…high thermal and chemical stability, high radiation resistance and insignificant leachability by water. [1][2][3][4][5][6][7][8] Rich crystal chemistry of phosphates with the variation of nature and ionic radius of cations have been explored in several reports. [6][7][8] In particular such phosphates with tetravalent ions form densely packed structure and they are amenable for immobilization of various actinides, like uranium, neptunium and plutonium.…”
Section: Introductionmentioning
confidence: 99%
“…Bregiroux [58]. On the opposite, lanthanide monophosphates with the monazite structure, show almost isotropic thermal expansion in the range of 9-10 Â 10 -6 K -1 [83].…”
Section: Thermal Expansionmentioning
confidence: 99%
“…Recently, Bregiroux et al revised the crystal structure and found that CaZr(PO 4 ) 2 actually crystallizes in the orthorhombic space group Pna2 1 (Z¼4) [58]. The coordination number of both cations is seven.…”
Section: Other Structuresmentioning
confidence: 99%
“…Spinels, which show ML under low velocity impact, are found to have cationic disorders by co-existence of inverse spinels. A peculiar connectivity of polyhedra of anion framework renders CaZr(PO4)2 fairly anisotropic in thermal expansion [193]. The occurrence of multiple traps with different depth in CaZr(PO4)2: Eu2+ is likely to provide more channels to release trapped electrons under strains in the process of ML.…”
Section: Mechanoluminescent Compoundsmentioning
confidence: 99%